Improved outcome of N-butyldeoxygalactonojirimycin-mediated substrate reduction therapy in a mouse model of Sandhoff disease. - Andersson, U; Smith, D; Jeyakumar, M; Butters, T; Borja, M; Dwek, R; Platt, F (2004)
Sandhoff disease is a severe neurodegenerative glycosphingolipid (GSL) lysosomal storage disorder, currently without treatment options. One therapeutic approach under investigation is substrate reduction therapy (SRT). By partially inhibiting GSL biosynthesis, the impaired rate of GSL catabolism is balanced by a slower rate of influx of GSLs into the lysosome. In a previous study, we reported the beneficial effects of treating Sandhoff disease mice with the glucose analogue N-butyldeoxynojirimycin (NB-DNJ), a compound that inhibits the first step of GSL biosynthesis catalysed by the ceramide specific glucosyltransferase. NB-DNJ, however, exhibits adverse effects at high doses such as weight loss and GI tract distress (due to glucosidase inhibition). This might limit the therapeutic potential of NB-DNJ for treating diseases affecting the CNS where high dose therapy may be required to achieve therapeutic levels of the drug in the brain. In the present study, a more selective compound, the galactose analogue N-butyldeoxygalactonojirimycin (NB-DGJ), was evaluated in the Sandhoff disease mouse model. Treatment with NB-DGJ showed greater therapeutic efficacy than NB-DNJ with no detectable side effects. The ability to escalate the dose of NB-DGJ, leading to extended life expectancy and increased delay in symptom onset, demonstrates the greater therapeutic potential of NB-DGJ for the treatment of the human gangliosidoses.